Steven C. Caton. "Peaks of Yemen I Summon"; Poetry as a Cultural Practice in a North Yemeni Tribe. Berkeley, Los Ángeles, Londres: University of California Press, 1990, xiii+351 pp. - Taboada, Hernán (Estudios de Asia y África, 1994)
-